Professional development: A potential mediator for enhanced teacher identity and positive organisational culture. - Harkin, Deirdre (Trinity College (Dublin, Ireland). School of Education, 2021)
The aim of this study is to identify examples in practice where a correlation between specific elements of professional learning and enhanced teacher practice is evident. In an era of extensive reform in the Irish education sector, ensuring professional development endeavours are successful in equipping teachers with the skills to meet diverse and complex student needs is essential to embed transformative change. The data revealed that professional development, specifically, how it is delivered and supported, has an impact on the way professional learning is enacted in practice. In addition, the data in this study suggests that professional learning can positively influence teachers’ professional identity, school cultures and attitudes to change. While previous research has established such links, this study aims to pinpoint aspects of a particular model of sustained professional development that have positively influenced identity, culture and attitudes to change. Experiential learning, coaching and modelling pedagogies, on-site learning and collaborative practice are identified as instrumental in terms of professional learning and practice change. This study acts as a springboard for further studies of a more longitudinal nature that could potentially identify more precisely a conceptual framework for professional development and its’ pivotal role in managing educational change.
Keywords: Leadership and Management; Education